Gymnastics as a cultural movement (Fiep Bulletin - online, 2015)
It is perhaps necessary to begin with a question: “ What is meant by “ voluntary gymnastics?” In The Belgian “ Gymnastique Educative” no 2/1954 I have found an article: “ Voluntary Gymnastics in France, Its aims – its organization”. In which is told that they try to introduce this voluntary gymnastics in france through “ La Fédèration Française de Gymnastique Educative”.
Keywords: .